Public Opinion and Policy Representation: On Conceptualization, Measurement, and Interpretation - Wlezien, Christopher (Policy studies journal, 2017)
The congruence between public preferences and public policy is of special importance in representative democracies. We want to know whether the public is getting the policies it wants and, if not, whose preferences are being represented. To directly evaluate congruence, scholars need to measure what the public wants in a particular policy area and then correctly match it to policy in that area. This is difficult to do. Not surprisingly, while much scholarship examines the congruence of positions, little research examines actual policy congruence. Even the work that there is on the subject offers limited information. In this paper, I assess what we can infer about congruence from the different scholarly traditions in the study of representation. I also consider prospects for research on the match between public preference inputs and public policy outputs, particularly when we cannot assess it directly. 摘要 公众偏好和公共政策的一致性在代表制民主中享有着特殊的重要意义。我们希望了解公众是否得到了他们想要的政策, 如果没有, 又是谁的偏好被代表了。为了直接评估这一一致性, 学者们需要测量在一特定政策领域公众所渴望的政策, 并与该领域的政策准确地匹配。这项工作是非常艰巨的。不足为奇的是, 尽管众多研究分析了位置的一致性, 鲜有研究审视实际政策的一致性。即便是那些讨论了这一主题的工作, 它们为我们提供的信息也非常有限。在本文中, 我分析了我们从代表制研究的不同学派中可以得到哪些和一致性相关的内容。我还展望了公众偏好输入和公共政策输出匹配度的相关研究的未来发展, 特别是当我们不能直接对其作出估计时。